2017
DOI: 10.5301/hipint.5000545
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Recommendations for Reducing Head-Neck Taper Connection Fretting Corrosion in Hip Replacement Prostheses

Abstract: There is fair evidence to recommend against the use of high offset femoral heads, larger diameter femoral heads, and to pay particular consideration to fretting corrosion's progression with time and risk with heavier or more active patients. Particular to metal-on-metal hip prostheses, there is fair evidence to recommend positioning the acetabular component to minimise edge loading. Particular to metal-on-polyethylene hip prostheses, there is fair evidence to recommend the use of ceramic femoral heads, against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Nevertheless, fretting corrosion may occur also at backside contacts in joint prostheses, bone-implant contact regions, overlapping cardiovascular stent contact points and other locations where surface contact and small cyclic motion exist [40]. Hence, fretting corrosion of biomaterials and implants has been studied extensively in the lab as well as on retrieved implants [40,68,142,143,271,329,330,331,332,333,334,335,336,337,338,339,340,341,342,343,344,345,346,347,348]. ASTM F1875 [349] specifies fretting corrosion testing of hip femoral head/bore and cone taper interface in modular implants.…”
Section: Mechanisms Of Corrosion In Vivomentioning
confidence: 99%
“…Nevertheless, fretting corrosion may occur also at backside contacts in joint prostheses, bone-implant contact regions, overlapping cardiovascular stent contact points and other locations where surface contact and small cyclic motion exist [40]. Hence, fretting corrosion of biomaterials and implants has been studied extensively in the lab as well as on retrieved implants [40,68,142,143,271,329,330,331,332,333,334,335,336,337,338,339,340,341,342,343,344,345,346,347,348]. ASTM F1875 [349] specifies fretting corrosion testing of hip femoral head/bore and cone taper interface in modular implants.…”
Section: Mechanisms Of Corrosion In Vivomentioning
confidence: 99%
“…We suspect that each of the implants underwent an extended process of chronic fretting to the point of failure due to the intra-operative findings consistent with chronic accumulation of metal particulate within the joint and findings consistent with cyclical wear. Concerns have been raised about increased risk of fretting with the use of high offset cobalt chromium femoral heads 10 and all 3 patients in this case series had high offset (8-10 mm), skirted cobalt chromium femoral heads. There have been other reports of TMZF femoral stem designs failing, most notably Rejuvenate stems, ABG II modular stems, 11 , 12 the Accolade I TMZF stems 13 , 14 and the Meridian TMZF stem.…”
Section: Discussionmentioning
confidence: 88%
“…Neither use samples with geometry representative of prostheses, which has been identified as important to performance clinically. 8 Although local crevice corrosion effects have been observed around fretting damage in pin-on-disc electrochemical studies, 73 neither potentiodynamic or EIS studies reproduce the crevice geometry critical to the MACC phenomenon. A pin-on-disc or similar test apparatus allows particles generated during a frettingcorrosion simulation to escape the region of interest.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…7 A systematic review of factors affecting head-neck taper connection fretting-corrosion included 91 studies but found inconsistent or inconclusive results for over 70% (25/35) of the factors investigated. 8 Inconsistent and inconclusive evidence may be the result of different study designs without appropriate consideration of This review seeks to highlight important considerations when developing in vitro test methods, to help researchers strengthen their study design and analyze the implications of others' design decisions. The advantages, disadvantages, limitations and procedural considerations for finite element analyses, electrochemical studies and in vitro simulations related to head-neck taper connection tribocorrosion are discussed (Table 1).…”
Section: Introductionmentioning
confidence: 99%